2018
DOI: 10.1371/journal.pone.0202773
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplasmonic pillars engineered for single exosome detection

Abstract: Exosomes are secreted nanovesicles which incorporate proteins and nucleic acids, thereby enabling multifunctional pathways for intercellular communication. There is an increasing appreciation of the critical role they play in fundamental processes such as development, wound healing and disease progression, yet because of their heterogeneous molecular content and low concentrations in vivo, their detection and characterization remains a challenge. In this work we combine nano- and microfabrication techniques fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 32 publications
0
64
0
Order By: Relevance
“…23,24 Examples of advanced exosomal analytical approaches include interferometry, 25 electrochemistry, 26,27 and optical sensors utilizing nanoplasmonics. 28,29 Recently, Rupert et al successfully demonstrated surface plasmon resonance (SPR) based sensing of CD63-positive exosomes through surface based immunocapture. 30 Collectively, the above-mentioned techniques provide a sensitive, label-free, and real-time assessment of exosomes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…23,24 Examples of advanced exosomal analytical approaches include interferometry, 25 electrochemistry, 26,27 and optical sensors utilizing nanoplasmonics. 28,29 Recently, Rupert et al successfully demonstrated surface plasmon resonance (SPR) based sensing of CD63-positive exosomes through surface based immunocapture. 30 Collectively, the above-mentioned techniques provide a sensitive, label-free, and real-time assessment of exosomes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, target exosomes could be detected at concentrations as low as 5 × 10 3 /mL by dual amplification between Au plate-Au nanoparticle and Au-Au nanoparticle. Raghu et al discussed Au nanoplasmonic pillar arrays developed using nano-and micro-fabrication techniques for single exosome detection by an LSPR imaging analytical method [90] (Figure 8a). By sizing the individual nanopillar to approximately 100 nm, similar to the size of an exosome, it is possible to observe in situ single-exosome binding events in sub-femtomolar concentrations of exosomes via LSPR imaging signal.…”
Section: Analytical Methods For Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…Flow cytometric techniques are beginning to elucidate single-EV biology (Marcoux et al, 2016 ; Stoner et al, 2016 ; Saugstad et al, 2017 ; Mastoridis et al, 2018 ; Tian et al, 2018 ; Kanada et al, 2019 ; Padda et al, 2019 ; Ricklefs et al, 2019 ; Zaborowski et al, 2019 ) and we expect to see significant growth in this area. There have also been a number of notable studies implementing nanoplasmonic technologies for single-EV detection and characterization (Im et al, 2014 ; Raghu et al, 2018 ; Rojalin et al, 2019 ).…”
Section: Experimental Approachesmentioning
confidence: 99%